1972
DOI: 10.1159/000460377
|View full text |Cite
|
Sign up to set email alerts
|

The Juvenile Baboon as a Model for Studies of Lead Poisoning in Children

Abstract: Lead toxicity has been studied in the juvenile baboon using both daily intravenous injections of lead chloride and ingestion of leaded paint and lead paint pigments. Approximate steady state blood lead concentrations of 0.9 and 0.08 mg% were obtained after one week of intravenous injections of either 5.0 and 0.5 mg of lead per day, respectively. The onset of clinical symptomatology was noted after only one week of 5.0 mg/day injections culminating in convulsions and blindness after 40 days. The interrelationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

1974
1974
1986
1986

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
2
11
0
1
Order By: Relevance
“…It is interesting that 14 of the affected primates were juveniles that varied in age from 6 to 30 months, while the remaining 20 animals were adults. Fisher (14) reported a case of lead poisoning in the gorilla, and Cohen et al (15) produced convulsions in baboons following the administration of lead. In addition, McIntosh (16) and Hausman et al (17) reported cases of lead intoxication in adult nonhuman primates.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…It is interesting that 14 of the affected primates were juveniles that varied in age from 6 to 30 months, while the remaining 20 animals were adults. Fisher (14) reported a case of lead poisoning in the gorilla, and Cohen et al (15) produced convulsions in baboons following the administration of lead. In addition, McIntosh (16) and Hausman et al (17) reported cases of lead intoxication in adult nonhuman primates.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Two reports describe infant to juve nile baboons fed small amounts of organic lead in paint [9,27], Oral admi nistration of inorganic lead has been reported in 16 adult [15], 20 juvenile [9,21,27], four infant [6], an unspecified number of infant, juvenile, and adult rhesus monkeys [2,11,24], and in eight infant [9] and one juvenile baboon [8]. Only one of these [8] received oral paint or paint pigment as the source of inorganic lead, and then, for only 180 days.…”
Section: Introductionmentioning
confidence: 99%
“…Precedent for this interpretation is found in the balance studies of Kehoe (14) who observed transient increases in blood lead concentration of similar magnitude in association with transient increases in the alimentary intake of lead. Similarly, recent studies in baboons (15) (18) and experimental data (1, 6) strongly implicate iron deficiency as the factor most likely to account for the marked difference in metabolic effect observed. Data in adults suggest that erythrocyte protoporphyrin is, perhaps, the most sensitive index of both latent and manifest iron deficiency (19).…”
Section: Data)mentioning
confidence: 57%